2013
DOI: 10.17795/acr-11979
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Growth Parameters in Children with Chronic Functional Constipation

Abstract: Background: Chronic functional constipation is an epidemic problem in children that has effects on the growth status. Objectives: The aim of this study is to evaluate the growth parameters in children with chronic functional constipation and compare them with healthy individuals. Patients and Methods: One hundred children with chronic functional constipation (defined as Rome III criteria) referred to Pediatric Gastroenterology Clinic enrolled in this study. Control group was consisted of 100 children who refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In a study by Ilan et al most of the children with constipation were obese or overweight (21). In a similar study conducted on 100 Iranian children younger than 18 years old with functional constipation Dehghani et al found a higher obesity rate and higher BMI and weight Z scores in constipated patients compared to healthy control group (22). Pawlowska et al demonstrated that pediatric patients with functional gastrointestinal disorders present various growth abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Ilan et al most of the children with constipation were obese or overweight (21). In a similar study conducted on 100 Iranian children younger than 18 years old with functional constipation Dehghani et al found a higher obesity rate and higher BMI and weight Z scores in constipated patients compared to healthy control group (22). Pawlowska et al demonstrated that pediatric patients with functional gastrointestinal disorders present various growth abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…A higher prevalence was detected by other authors, such as a 22.3% rate among constipated adolescents enrolled in a high school in the city of dos Campos (Brazil) [14], 35% rate in a study conducted by Trisóglio et al [18] among students of a faculty of medicine in the interior of the state of São Paulo, and a 40% rate detected by Jamie et al among university students in the city of Goiânia (Brazil) [6]. In these studies there was a statistically significant predominance of teenage girls, as also observed by Zaslavsky et al in a study of 48 adolescents with intestinal constipation seen at the University Hospital of Porto Alegre [20] and by Dehghani et al [21] among adolescents attended at a gastroenterology service in Iran.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, in the studies performed by Dehghani et al 4 , there was the systemic review of van den Berg et al, which demonstrated no considerable differences between the genders. 5 Striking disparity in the weight between two groups could have resulted either from the anorexia in the domain of FC that varies from 10% to 38% in these patients, or from silent undiagnosed CD.…”
Section: Discussionmentioning
confidence: 83%
“…[1][2][3] The most common initiator of FC in childhood is an experience of painful defecation. 4 The estimated prevalence of FC is between 0.3% to 8% of pediatric population that is different according to race and geographic regions. 2,4 The FC is diagnosed based on Rom III criteria and there is no need for laboratory workup except for precise history and physical examination, [1][2][3][4][5] though some authors suggest evaluation for celiac disease (CD) in constipated patients especially in severe and refractory cases before making the diagnosis of FC in such patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation